The multiple functions of CD5 in diseases related to immune disorders - Jiawen Dong; Kaibo Zhang; Jinhui Hong; Jialu Ye; Leping Wang; Qiang Ke; Yuyang Ye; Keting Jin; Yalun Chen; Jing Wu (Annals of Medicine)
CD5 is a critical regulator of the immune system and a transmembrane glycoprotein expressed on T cells and the surface of certain B cells. Over the years, numerous studies have demonstrated that CD5 is involved in the regulation of immune responses, maintenance of immune tolerance, and modulation of cell survival and apoptosis. Beyond these functions, CD5 also plays a role in immunotherapy, recognition of pathogen-associated molecular patterns, regulation of inflammatory processes, prediction of poor tumour prognosis, and clearance of macromolecules. Immune aberrant disorders—such as infections, chronic inflammation, malignancies, and autoimmune diseases—arise when the immune system becomes dysregulated. This study outlines the diverse and extensive biological functions of CD5 in relation to immunological abnormalities. A deeper understanding of CD5’s specific roles in disease is expected to shed light on the complex pathophysiology of these conditions and may reveal novel therapeutic strategies and interventions for the management of immune-related disorders.